Economic and Environmental Policy Issues in Indian Textile and Apparel Industries - Gopalakrishnan, Badri Narayanan (SpringerBriefs in Environmental Science, 2018)
This book comprehensively reviews, as well as analyzes, various aspects related to the Indian textile and apparel industries. While the focus is on economic and environmental issues, the discussion covers a lot of policy elements. The approach is inter-disciplinary, with concepts drawn from economics, environmental science, history, chemistry, textile technology and quantitative methods/optimization literature. This book will appeal to several stakeholders such as, policy researchers, policy-makers in governmental and international agencies, academicians and students from all the disciplines mentioned above, industrialists, managers and consultants working on Indian textile and apparel sectors. It might also provoke interest among as well as agriculturalists, farm policy analysts and industrialists focusing on other products such as chemicals, plastics, machineries, etc., who are wholly or partly dependent on textile and apparel industry in India.